#### Answer

$= -\frac{x-3}{x-2}$

#### Work Step by Step

$\frac{x-3}{x-6} \div \frac{x-2}{6-x}$
$= \frac{x-3}{x-6} \times \frac{6-x}{x-2}$
$= \frac{x-3}{x-6} \times \frac{-(x-6)}{x-2}$
$= \frac{x-3}{1} \times \frac{-1}{x-2}$
$= -\frac{x-3}{x-2}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$= -\frac{x-3}{x-2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.